Monodipserse Nanostructured Spheres of Block Copolymers and Nanoparticles via Cross-Flow Membrane Emulsification - Shin, Jae Man; Kim, Minsoo P.; Yang, Hyunseung; Ku, Kang Hee; Jang, Se Gyu; Youm, Kyung Ho; Yi, Gi-Ra; Kim, Bumjoon J. (AMER CHEMICAL SOC, 2015)
Monodisperse colloidal particles of polystyreneb-polybutadiene (PS-b-PB) block copolymers (BCPs) were successfully prepared, in which uniform emulsions containing BCPs were first generated by cross-flow membrane emulsification using tubular Shirasu porous glass (SPG) membrane, and then unique internal nanostructures were developed by controlled evaporation of solvent inside emulsion. The diameter of those BCP particles could be controlled from 200 nm to 5 mu m by tuning the pore diameter of the membrane. With symmetric BCPs, onion-like nanostructures inside particles were formed. Coiled cylinders in the BCP particles were also developed by adding homopolymers, in which the assembled BCP structure is strongly dependent on the particle size, demonstrating the importance of our membrane method in generating monodisperse BCP particles. Further investigation of process parameters showed that for a given pore diameter, the operation pressure (P) and surfactant concentration were critical parameters for narrow size distribution of the particles. Uniform emulsions were produced when the ratio of the operation pressure to the critical pressure (P/Pc) was less than 4.33. In addition, uniformly sized, hierarchically structured particles of BCPs and nanopartides (NPs) were produced, in which oleylamine-coated, 3 nm sized Au NPs were incorporated selectively into the PB domains inside the particles.
Keywords: DIBLOCK COPOLYMERS; FACILE SYNTHESIS; MICROSPHERES; PARTICLES; EMULSIONS; SIZE; FABRICATION; MORPHOLOGY; PHASES; SHAPE